2020
DOI: 10.1093/noajnl/vdaa113
|View full text |Cite
|
Sign up to set email alerts
|

Features of tumor texture influence surgery and outcome in intracranial meningioma

Abstract: Objective Texture-related factors such as consistency, vascularity and adherence vary considerably in meningioma and are thought to be linked with surgical resectibility and morbidity. However, data analyzing the true impact of menigioma texture on the surgical management is sparse Methods Patients with intracranial meningioma treated between 08/2014-04/2018 at our institution were prospectively collected for demographics, cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Highly vascularized meningiomas pose a different set of challenges to the neurosurgeon than less vascular tumors. 29 We found that larger tumors and the presence of PTBE were significantly associated with the number of arterial feeders. The average number of feeding vessels did not differ between skull base and NSBM in our study.…”
Section: Discussionmentioning
confidence: 62%
“…Highly vascularized meningiomas pose a different set of challenges to the neurosurgeon than less vascular tumors. 29 We found that larger tumors and the presence of PTBE were significantly associated with the number of arterial feeders. The average number of feeding vessels did not differ between skull base and NSBM in our study.…”
Section: Discussionmentioning
confidence: 62%
“…Texture characteristics might imply the toughness of operations. 40 Consequently, radiomics could be used to predict CMS. Owing to the lack of similar studies, the further underlying mechanisms between these radiomics features and CMS are unclear, and need to be validated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Invasiveness reflects the extent how brain tissue is infiltrated by the tumor. Texture characteristics might imply the toughness of operations 40 . Consequently, radiomics could be used to predict CMS.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor texture can influence surgical morbidity and outcome as recently shown for intracranial meningiomas. 48 Based on imaging characteristics and growth patterns, SM can usually be differentiated from other intradural extramedullary spinal cord lesions such as neurofibroma and schwannoma. Signal intensity ratio of the spinal tumor and fat on T2 weighted images is useful for differentiating schwannomas from meningiomas to obtain an accurate diagnosis.…”
Section: Clinical Presentation and Diagnosismentioning
confidence: 99%